Writers in the Schools : A Guide to Teaching Creative Writing in the Classroom - Brooks, Jeanice; Stephens, Matthew; Thormählen, Wiebke (Book collections on Project MUSE., 2022)
"Sound Heritage is the first study of music in the historic house museum, featuring contributions from both music and heritage scholars and professionals in a richly interdisciplinary approach to central issues. It examines how music materials can be used to create narratives about past inhabitants and their surroundings - including aspects of social and cultural life beyond the activity of music making itself - and explores how music as sound, material, and practice can be more consistently and engagingly integrated into the curation and interpretation of historic houses. The volume is structured around a selection of thematic chapters and a series of shorter case studies, each focusing on a specific house, object or project. Key themes include: Different types of historic house, including the case of the composer or musician house; what can be learned from museums and galleries about the use of sound and music and what may not transfer to the historic house setting; Musical instruments as part of a wider collection; questions of restoration and public use; and the demands of particular collection types such as sheet music; Musical objects and pieces of music as storytelling components, and the use of music to affectively colour narratives or experiences. This is a pioneering study that will appeal to all those interested in the intersection between Music and Museum and Heritage Studies. It will also be of interest to scholars and researchers of Music History, Popular Music, Performance Studies and Material Culture"--